Turystyka przygraniczna w województwie śląskim - wybrane aspekty - Jankowski, Andrzej T.; Nitkiewicz-Jankowska, Anna (Selected Aspects of Tourism in Border Regions Based on the Example of Silesia Province, 2005)
The areas at-the-border are very special in many respects. Essential conditions to create an attractive tourist product, such as at the border tourism, are tourist and paratourist investments based on proper putting existing natural and anthropogenic qualities in working order and making them accessible. Undoubtedly, the most important advantages of the at-the-border tourism on the area of Silesian province are: natural and cultural richness of the region, well but not steadily developed accommodation and eating facilities, accompanying increasing number of better and better national, local and international roads, low prices attracting foreign tourists aimed at shopping. However, this tourist product numerous weaknesses and threats, there are real chances to improve the quality of at-the-border tourism with Poland's southern neighbours.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 105-109